ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGGAJIAN DAN UPAH PADA PT RIMBA PRAJNA MULIA - Emmanuel, Arie; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2017)
Accordance to the nowadays development of information and technology, companies have to compete one to each others. In order to face the competition, one of the most important thing that need attention is human resources that connected to salary and wages. PT. Rimba Prajna Mulia took a lot of attention for this factor because all of the process for salary and wages in the company used the manual process without a system that able and suitable that occur delays on the payment process. This problems prompt writter to start research to analyse the old system, redesign the system models based on the result from analysis using the Unified Modeling Languange (UML) and design the system prototype for the ccompany so the ccompany will have a system that able to afford the internal control for the company and provide the reports that needed by management in taking the future decisions.